Implementation of the Problem Based Learning Model Assisted with Google Sites to Improve Concept Understanding and Reduce Students' Mathematical Anxiety - Sih Mustika, Gandes; Astuti, Dwi; Aprilia, Anna; Yuliandari, Yuliandari (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This research explores the effectiveness of problem-based learning (PBL) with Google Sites in improving concept comprehension and reducing math anxiety among 36 class X students at SMA N 1 Sewon. Following Kemmis and Mc Taggart's model, the study consisted of two cycles, each with two meetings. Data collection involved observation sheets, concept tests, and anxiety questionnaires. The success criteria were set at over 70% of students achieving high concept understanding and low anxiety. Results indicate significant improvements in both areas. Between pre-action and cycle I, students' understanding increased by 65.97%, with a further 40.28% increase between cycles I and II. The anxiety decreased by 7.73% and 9.03% between the respective periods. By cycle II, 83.33% of students demonstrated high concept understanding, and 80.56% reported low anxiety, meeting the success criteria. This suggests that PBL with Google Sites effectively enhances concept comprehension and reduces math anxiety among class X students.